Association Between Preterm Birth and Chronic Toxoplasma gondii Infection in Latina Women [04A]. (May 2020) - Ranaweera, Indira; Ozorio Dutra, Samia Valeria; Yoo, Ji Yoon; Louis-Jacques, Adetola; Duffy, Allyson; Groer, Maureen
Abstract : INTRODUCTION: Chronic Toxoplasma gondii infects up to one-third of the world's population. Latina women have a higher rate of infection with more virulent serotypes. While acute infection can cause devastating effects in pregnancy, chronic infection had not been considered to have pathological effects. Our objective is to investigate the association between preterm birth and chronic T. gondii infection in Latina women. METHODS: We evaluated 178 Latina women for T. gondii status and followed them through pregnancy and up to 6 weeks postpartum. Demographic information, obstetric histories, pregnancy outcomes, and blood samples were obtained. T. gondii IgG positivity signified chronic exposure. We performed descriptive analyses, chi-square, and Student t-test. RESULTS: There were complete data on 157 Latina women. Thirty-three (21.0%) were T. gondii IgG positive and 124 (79.0%) were T. gondii IgG negative. Among T. gondii positive women, 9 (27.3%) delivered preterm as compared to 15 (12.1%) of T. gondii negative women. There was a significant difference when comparing the frequency of preterm birth in T. gondii IgG positive and T. gondii IgG negative mothers (phi coefficient=.172, P <.031). The mean gestational age of delivery was 36.9 weeks (SD±3.98) for seropositive mothers and 38.1 weeks (SD±2.96) for seronegative mothers (t(155)=1.931, P =.055). CONCLUSION: T. gondii IgG seropositivity was associated with a higher likelihood of preterm delivery in Latina women. Further studies are needed to examine the impact of chronic T. gondii infection on pregnancy outcomes.